2017
DOI: 10.1007/s10120-016-0687-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of laparoscopy-assisted distal gastrectomy with suprapancreatic nodal dissection for clinical stage I gastric cancer: a multicenter phase II trial (JCOG0703)

Abstract: Background Laparoscopic gastrectomy has become a common surgical treatment for gastric cancer in eastern Asian countries. However, a large-scale prospective study to investigate the benefit of laparoscopy-assisted distal gastrectomy (LADG) regarding long-term outcomes has never been reported. We have already reported the shortterm outcomes of this study. Here we report long-term outcomes as the secondary endpoints of this study after a 5-year follow-up period. Methods This study comprised patients with clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
2
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 19 publications
2
49
2
1
Order By: Relevance
“…Since, younger patients have less comorbidities and longer expectancy than elderly, fine classification of patients is needed to compare the surgical short-and long-term outcomes, as in our study. The JCOG0703 study in which the majority of the patients were pathological Stage I, has shown that no patients had recurrent disease and the 5-year OS and RFS were both 98.2% (17). Although, in that study the median age was 59 years old, a similar result was obtained in the current study: no patients had recurrent disease in pathological Stage I.…”
Section: Discussionsupporting
confidence: 85%
“…Since, younger patients have less comorbidities and longer expectancy than elderly, fine classification of patients is needed to compare the surgical short-and long-term outcomes, as in our study. The JCOG0703 study in which the majority of the patients were pathological Stage I, has shown that no patients had recurrent disease and the 5-year OS and RFS were both 98.2% (17). Although, in that study the median age was 59 years old, a similar result was obtained in the current study: no patients had recurrent disease in pathological Stage I.…”
Section: Discussionsupporting
confidence: 85%
“…Laparoscopic gastrectomy (LG) with lymphadenectomy is increasingly performed to manage early gastric cancer in Asian countries because of its reduced invasiveness compared with conventional open gastrectomy [1][2][3][4][5][6]. However, because the incidence of lymph node (LN) metastasis is low in early gastric cancer, LN dissection during LG may be overly invasive for patients with pathological N0 disease.…”
Section: Introductionmentioning
confidence: 99%
“…Some well-designed multicenter randomized controlled trials (RCTs) from Japan (JCOG0912 [5]) and Korea (KLASS-01 [6]) revealed that LADG was just as safe as conventional ODG in terms of short-term clinical outcomes for stage I gastric cancer, even with significantly lower overall complication rate [6]. Furthermore, the long-term outcomes of EGC patients undergoing LADG were proven comparable to those of patients treated by ODG from a single-arm, multi-institutional clinical trial (JCOG0703 [7]).…”
mentioning
confidence: 99%